The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11886-014-0502-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomics of the 9p21.3 Locus for Atherosclerosis: Clarity or Confusion?

Abstract: The 9p21.3 locus was the first to yield to genome-wide association studies (GWAS) seeking common genetic variants predisposing to increased risk of coronary artery atherosclerotic disease (CAD). The 59 single nucleotide polymorphisms that show highest association with CAD are clustered in a region 100,000 to 150,000 base pairs 5' to the cyclin-dependent kinase inhibitors CDKN2B (coding for p15(ink4b)) and CDKN2A (coding for p16(ink4a) and p14(ARF)). This region also covers the 3' end of a long noncoding RNA tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 98 publications
0
23
0
Order By: Relevance
“…The 9p21.3 locus was the first one identified by GWAS, consisting of a cluster of 59 linked SNPs in a 53,000-bp region [30]. Among the CAD risk alleles, rs10811656 and rs10757278 are located in an enhancer element and disrupt a binding site for ATAT1 [31].…”
Section: Discussionmentioning
confidence: 99%
“…The 9p21.3 locus was the first one identified by GWAS, consisting of a cluster of 59 linked SNPs in a 53,000-bp region [30]. Among the CAD risk alleles, rs10811656 and rs10757278 are located in an enhancer element and disrupt a binding site for ATAT1 [31].…”
Section: Discussionmentioning
confidence: 99%
“…Targeted deletion of the orthologous ANRIL risk interval in mice can reduce expression of CDKN2A and CDKN2B in the heart and lead to excessive proliferation of vascular cells [36]. Indeed, subsequent studies showed that ANRIL expression is associated with the risk for coronary atherosclerosis, carotid arteriosclerosis, peripheral artery disease, and other vascular diseases [14, 16, 37, 38]. Carriers of the risk alleles showed increased whole blood RNA levels of ANRIL short variants DQ485454 and EU741058.1 , whereas the long variant DQ485453 was decreased [9].…”
Section: Discussionmentioning
confidence: 99%
“…Second, this region is a gene desert, lacking known coding genes, with the closest genes being the cell-cycle inhibitors CDKN2A and CDKN2B . Third, although the region encompasses the terminal exons of a long non-coding RNA (lncRNA), ANRIL (also known as CDKN2B-AS1 ), and is predicted to be enhancer rich, both lncRNA function and enhancer activity are difficult to assess using purely computational tools and are often highly context-dependent (Hannou et al, 2015; Chen etal., 2014). …”
Section: Introductionmentioning
confidence: 99%